Surfactant Monolayer Bending Elasticity in Lipase Containing Bicontinuous Microemulsions - Engelskirchen, Sandra; Wellert, Stefan; Holderer, Olaf; Frielinghaus, Henrich; Laupheimer, Michaela; Richter, Sven; Nestl, Bettina; Nebel, Bernd; Hauer, Bernhard (Frontiers in Chemistry, 2021)
Lipase catalyzed reactions offer many advantages amongst which a high degree of selectivity combined with the possibility to convert even non-natural substrates are of particular interest. A major drawback in the applicability of lipases in the conversion of synthetically interesting, non-natural substrates is the substantial insolubility of such substrates in water. The conversion of substrates, natural or non-natural, by lipases generally involves the presence of a water-oil interface. In the present paper, we exploit the fact that the presence of lipases, in particular the lipase from Candida antarctica B (CalB) changes the bending elastic properties of a surfactant monolayer in a bicontinuous microemulsion consisting of D2O/NaCl - n-(d)-octane - pentaethylene glycol monodecyl ether (C10E5) in a similar manner as previously observed for amphiphilic block- copolymers. To determine the bending elastic constant, we have used two approaches, small angle neutron scattering and neutron spin echo spectroscopy. The results allow to derive further information on the influence of CalB on the composition and bending elasticity of the surfactant monolayer itself as well as the underlying adsorption/desorption mechanism.